Ultrafast formation of an FeOOH electrocatalyst on Ni for efficient alkaline water and urea oxidation - Zhang, Jun-Jun; Bao, Wei-Wei; Li, Meng-Yang; Yang, Chun-Ming; Zhang, Nan-Nan (Chemical communications (Cambridge, England), 2020)
We report FeOOH supported on Ni foam which enables highly efficient UOR electrocatalysis and can be readily produced through a hydrolysis reaction. Our developed UOR catalyst as the anode can provide a current density of 200 mA cm −2 at 1.427 V vs. RHE, as well as remarkable operational stability, representing the best yet reported noble metal-free urea electrolyser. The developed UOR electrocatalyst as the anode can provide a current density of 200 mA cm −2 at 1.427 V vs. RHE, as well as remarkable operational stability.